Heat Transfer Measurement on a Turbulent Spot Using the Energy Balance Method - Chaiworapuek, Weerachai; Nongnoi, Suttaya; Kittichaikarn, Chawalit (Agriculture and Natural Resources, 2014)
A turbulent spot is a small turbulent patch, surrounded by laminar ﬂow at a boundary layer transition. It is an important mechanism, clearly showing the characteristics of highly turbulent ﬂow and heat transfer inside the body. However, measurement in heat transfer from a ﬂat plate to a ﬂuid via a turbulent spot remains difﬁcult due to the unsteady and unstable nature of the site. This paper detailed a temperature measurement technique using a coating of thermochromic liquid crystal. An analytical solution, derived from the developed energy balance method and an image processing technique were combined to visualize the thermal footprint of a turbulent spot. The experiment was performed over an isothermal ﬂat plate in a low turbulence water tunnel where the turbulent intensity was lower than 1%. Reynolds number was initially kept at 75,000, as a reference rate for laminar ﬂow. Transitional ﬂow was bypassed by a small disturbance injection. The results were presented qualitatively and quantitatively using color, temperature, the heat transfer coefﬁcient and heat ﬂux as spots were propagated downstream. The locations of the leading and trailing edges were also clearly visualized. Turbulent spot information (spot celerities and the half spreading angle) were in agreement with those obtained by the other researchers, conﬁrming the reliability of this technique. Thus, this energy balance method can be applied effectively to obtain insight into the bypass boundary layer transition over a ﬂat plate.